Limitations of the strategy of healthy municipalities as public policy in Antioquia - Blanca M. Chávez G (Universidad de Antioquia, 2009)
Objective: To evaluate the process of formulating and implementing of the healthy cities strategy as public policy in Antioquia, Colombia, between 2001 and 2005. Methodology:The research has two components, one quantitative and qualitative. This article only developes part of the qualitative component. Techniques used for this component were semistructured interviews and focus groups, which were applied to departmental officials and subregional and local actors in institutions and communities involved. Results: Of the categories analyzed, three did not favor the implementation of public policy. 1) The imposition of public policy by the government to municipalities, 2) the immaturity of public institutions and political processes and local department, 3) the lack of building political will. They triggered an unsuccessful experience of public policy. Conclusions:Healthy Municipalities public policy was a strategy of regional government that lacked the discussion and negotiation with local actors and build political will over time the political system and administrative structure to achieve its development effectiveness